Sexual Abuse Whirlpool: Characteristics of Abuse (Type, Perpetrator-Victim Relation, Psychological Reactions of Victims), Parents’ Attitudes and Behaviours of Abusers (Grooming Methods): Sexual Abuse Whirlpool - Gönültaş, Burak Miraç (The Bulletin of Legal Medicine, 2021)
Aim: This study aims to analyze (n=175) sexual abuse cases conducted in Istanbul between 2009-2012 by making use of a qualitative method and to describe characteristics of the cases, the attitudes of the parents and the methods of grooming of the abusers by making a holistic assessment. Materials and Methods: Qualitative analysis method was used in this study. For data, the document analysis procedure according to the Journal Article Reporting Standards for Qualitative Research (JARS-Qual) standards and the research design recommended by the American Psychological Association were followed. A coding table was constructed and data were analyzed through coding table. Results: The victims (n=202) were mostly girls and average age was 11.4. They were mostly exposed to penetration-related abuse (52%). The abusers were mostly from intimates of the victim (57%). Most of the abuses took place at the perpetrator’s home or in a place he/she knew (65,8%). The majority of parents learned about the abuse during the investigation (56%). Abusers applied to methods such as promises, bribes, threats, coercion to approach children and become physically closest. Bribes, warnings and threats were used to prevent the child from disclosing it after the abuse (70%). Conclusion: Children appear to be quite vulnerable due to a number of circumstances before and after the case of abuse. This vulnerability leads them to be exposed into the act of abuse, and prevents them from disclosing the abuse. The conditions leading to vulnerability have been assessed as a whole and defined as a “sexual abuse whirlpool”.